DEVELOPING TEXT CONSTRUCTION SKILLS IN PRIMARY SCHOOL STUDENTS (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the essence, significance, and effective methodological approaches to the formation and development of text creation skills among primary school students.
Keywords: Primary education, text creation, written speech, skill, language development, methodology, didactics.